Analysis of psychic trauma in contemporary psychoanalytic production (Research, Society and Development, 2022)
This article sought to address the issue of trauma in its contemporary psychoanalytic education. The aim of the article is to explore the theoretical complexity that permeates the concept of trauma in psychoanalysis, its repercussions on the subject's suffering and life history, and the forms of expression of psychological suffering today. In Freud and Lacan we have formulations that provide the theoretical framework for a thorough analysis of the conception of trauma. The selected material started from a bibliographic survey at the Virtual Health Library (VHL) and after the compilation of the texts, we used psychoanalytical discourse analysis as reading of the materials. We verified the different conceptions of trauma present in relation to the conception of trauma in psychoanalytic production, highlighting the relevance of the external factor in the examined researches, as a producer of psychic suffering, and the fundamental importance of the listening place, provided by the analyst, for elaboration of trauma on the part of the subject.